Fuelling genetic and metabolic exploration of C3 bioenergy crops through the first reference transcriptome of Arundo donax L. Issue 5 (20th February 2014) - Sablok, Gaurav; Fu, Yuan; Bobbio, Valentina; Laura, Marina; Rotino, Giuseppe L.; Bagnaresi, Paolo; Allavena, Andrea; Velikova, Violeta; Viola, Roberto; Loreto, Francesco; Li, Mingai; Varotto, Claudio
Summary The development of inexpensive and highly productive biomass sources of biofuel is a priority in global climate change biology. Arundo donax, also known as the giant reed, is recognized as one of the most promising nonfood bioenergy crops in Europe. Despite its relevance, to date no genomic resources are available to support the characterization of the developmental, adaptive and metabolic traits underlying the high productivity of this nonmodel species. We hereby present the first report on the de novo assembly of bud, culm, leaf and root transcriptomes of A. donax, which can be accessed through a customized BLAST server (http://ecogenomics.fmach.it/arundo/) for mining and exploring the genetic potential of this species. Based on functional annotation and homology comparison to 19 prospective biofuel Poaceae species, we provide the first genomic view of this so far unexplored crop and indicate the model species with highest potential for comparative genomics approaches. The analysis of the transcriptome reveals strong differences in the enrichment of the Gene Ontology categories and the relative expression among different organs, which can guide future efforts for functional genomics or genetic improvement of A. donax. A set of homologs to key genes involved in lignin, cellulose, starch, lipid metabolism and in the domestication of other crops is discussed to provide a platform for possible enhancement of productivity and saccharification efficiency in A. donax.